Mesenchymal Chondrosarcoma of the Parotid Gland (Bangladesh Journal of Otorhinolaryngology, 2020)
Mesenchymal Chondrosarcomas of the parotid are extremely rare tumours. They are broadly classified under extra skeletal form of mesenchymal chondrosarcomas and account for less than 1% of all sarcomas. It is characterized by a multinodular architecture, abundant myxoid matrix, and malignant chondroblast like cells arranged in cords. The tumor is an entity from chondrosarcomas of bones, commonly found in the soft tissues of the lower extremities at 80%. There are very limited reports of this tumor in the head and neck, especially in the parotid gland. We report a rare case of a parotid mesenchymal chondrosarcoma in a 55 years old man and discuss the pathogenesis, clinical presentation and management of such a rare tumourBangladesh J Otorhinolaryngol; October 2020; 26(2): 158-160